2009
DOI: 10.1177/1756285608100427
|View full text |Cite
|
Sign up to set email alerts
|

Review: The potential for estrogens in preventing Alzheimer's disease and vascular dementia

Abstract: Estrogens are the best studied class of drugs for potential use in the prevention of Alzheimer's disease (AD). These steroids have been shown to be potent neuroprotectants both in vitro and in vivo, and to exert effects that are consistent with their potential use in prevention of AD. These include the prevention of the processing of amyloid precursor protein (APP) into beta-amyloid (Aβ), the reduction in tau hyperphosphorylation, and the elimination of catastrophic attempts at neuronal mitosis. Further, epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 242 publications
(338 reference statements)
0
44
0
1
Order By: Relevance
“…Therefore, females experience higher age-specific AD death rates [49]. It is reported that estrogen has a profound effect on altering AD progression [50] with nearly complete loss of estrogen following menopause related to AD in women [51]. Lower levels of estrogen in women with AD have been reported during the various endocrinological evaluations [52, 53].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%
“…Therefore, females experience higher age-specific AD death rates [49]. It is reported that estrogen has a profound effect on altering AD progression [50] with nearly complete loss of estrogen following menopause related to AD in women [51]. Lower levels of estrogen in women with AD have been reported during the various endocrinological evaluations [52, 53].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%
“…In general, although not always, CPS increases depressive and anxious behavior to a greater extent in female offspring, but impairs cognition more in the males [38,39]. Further, estrogens could prevent the processing of A␤PP into A␤ and reduce the tau hyperphosphorylation [22]. Which is why male offspring were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…7D for more details). Two-way ANOVA analyses showed that both CPS and COS significantly increased A␤ 42 protein (F (1,22) = 7.307, p = 0.013 for CPS; F (1,22) = 25.202, p < 0.001 for COS). Post hoc analyses revealed a significant increase in hippocampal A␤ 42 in the CPS + COS group, compared to all other groups (p < 0.001 for Control, p = 0.020 for COS-treated, p = 0.001 for CPS-treated).…”
Section: Expression Of Aβ 42 Protein Detected By Elisamentioning
confidence: 98%
See 1 more Smart Citation
“…Prior to publications of the Women’s Health Initiative (WHI) and Women’s Health Initiative Memory Study (WHIMS) (39)(40) (41)(42), hormone therapy (HT) was thought to be neuroprotective and a large body of basic science and generally supportive epidemiological evidence suggested that HT reduced the risk of Alzheimer’s Disease (AD) by approximately 50% (see reviews (43) (44)). Approach to hormone therapy (HT) changed radically however, following the results of the WHI and WHIMS.…”
Section: Implications Of the Whims Studymentioning
confidence: 99%